Progress in optical networking. - Green, P.
This article summarizes the present state of optical networking, how we got to this point, and what needs to be done to complete the job. The point of departure is an assumed future two-level structure in which the transport is by means of steadily growing interconnected all-optical islands of transparency, while the remainder of the communication layers are based on IP, both levels being managed by an MPLS-based control plane. After reviewing why such networks are becoming inevitable, a review is given of the various optical layer technology and architecture bottlenecks that have had to be solved. Issues that remain center on increasing the number of channels and reducing the technology costs
Keywords: DWDM; IP; MPLS-based control plane; SDH; SONET; Channels; Communication layers; Dense wavelength division multiplexing; Interconnected all-optical islands; Optical architecture bottlenecks; Optical crossconnects; Optical fiber transport; Optical layer technology; Optical networking; Synchronous digital hierarchy; Synchronous optical network; Technology costs reduction; Two-level structure